موقف سيد القمني من السنة النبوية - دراسة نقدية - - رياض مخلوف (université d'eloud, 2026)
الحمد لله وحده والصلاة والسلام على من لا نبي بعده وبعد: فهذا ملخص البحث المعنون بــ: "موقف سيد القمني من السنة النبوية -دراسة نقدية-" وهو الأطروحة المقدمة لنيل شهادة الدكتوراه ل.م.د تخصص "دراسات حديثية معاصرة"، إعداد الطالب: رياض مخلوف وبإشراف د. محمد رمضاني. وقد عالج هذا البحث إحدى القراءات المعاصرة للتراث الإسلامي المتمثلة في موقف الكاتب والمفكر المصري الراحل سيد القمني من السنة النبوية في ضوء ما يُسمّى بالتنوير الفكري؛ بهدف مواكبة ما استجد في دنيا المعرفة واللحاق بالركب الحضاري، حيث أماط هذا البحث اللثام عن مواقع الخلل ومكامن الخطر في رؤية سيد القمني إلى مفهوم السنة النبوية وما اتصل بها من مهمات مسائل السنة، حيث تمحورت الأطروحة حول أربعة فصول: أوّلها الفصل التمهيدي الذي تضمن تعريفا بسيد القمني ولمحةً عن أهم تصوراته الفكرية المرتبطة بأصول العقيدة الإسلامية مع إيراد أهم الدعائم والمنطلقات التي عول عليها في قراءته للتراث، ليأتي الفصل الأول الذي تَناولَ رأيَه في مفهوم السنة النبوية ونشأتها، ثم الفصل الثاني الذي عالج موقفه من قضيتي تدوين السنة النبوية وحجيتها، ثم الفصل الأخير الذي خُصِّص لبحث مسألتين من مهمات علم أصول الحديث، والتي تُمثل في بعض جوانبها آليات نقل السنة النبوية، وهما مسألة عدالة الصحابة ومسألة التواتر والآحاد. وقد انتهى البحث إلى تحليل ونقد ومناقشة جل مواقف سيد القمني السالفة، والتي كانت غاية في السلبية ومخالفة الواقع العلمي، لا سيما تلك التي تعلقت بشخص النبي  وأقواله وأفعاله وسائر تصرفاته، كما كشفت عن هزال وضَعة المستوى العلمي لسيد القمني سواء من جهة المنهجية العلمية والإخلال بأهم خصائص وقواعد البحث العلمي، وفي طليعتها الموضوعية والإنصاف والأمانة العلمية، أو من جهة القصور في العلوم الأصلية المقاصدية أو العلوم الآلية المساعدة كعلم أصول الحديث، والتي ألقت بسيد القمني في أغلاط ومغالطات لا تغتفر. Abstract: All praise is due to Allah alone, and peace and blessings be upon the one after whom there is no prophet. This is a summary of the doctoral dissertation titled “Sayyid al-Qimni’s Position on the Prophetic Sunnah – A Critical Study,” submitted by the doctoral candidate Riyadh Makhlouf under the supervision of Dr. Mohammed Ramdhani, in partial fulfillment of the requirements for a PhD degree in Contemporary Hadith Studies. The study delves into one of the contemporary reinterpretations of Islamic heritage, focusing on the perspective of the late Egyptian writer and thinker Sayyid al-Qimni regarding the Prophetic Sunnah, particularly within the framework of what is commonly referred to as intellectual enlightenment or the renewal of religious discourse. The aim is to assess how these modern trends seek to align Islamic thought with evolving knowledge and global developments. The thesis critically investigates the key flaws and potential dangers in al-Qimni’s understanding of Sunnah and related core Hadith issues. It consists of four chapters: the introductory chapter offers a brief biography of Sayyid al-Qimni and highlights his intellectual foundations concerning Islamic creed, as well as the assumptions underpinning his approach to Islamic heritage; the first chapter discusses his view of the concept and origins of the Sunnah; the second addresses his position on the documentation and authority of the Sunnah; and the final chapter examines two significant issues in Hadith methodology, the credibility of the Prophet’s Companions and the distinction between mass-transmitted (mutawatir) and solitary (ahad) reports, as key elements in the transmission of Sunnah. The research ultimately concludes that most of al-Qimni’s views are marked by substantial academic shortcomings and a serious detachment from scholarly integrity, particularly in his treatment of the Prophet’s (peace and blessing be upon him) sayings, actions, and character. His approach is also shown to lack scientific rigor, objectivity, and fairness, reflecting weak methodological grounding and an insufficient grasp of both core Islamic sciences and auxiliary disciplines such as Hadith principles, leading to serious intellectual errors that cannot be overlooked.
أطروحة دكتوراء
Keywords: سيد القمني; السنة النبوية; موقف; المذاهب الفكرية المعاصرة